The Effectiveness of Acupressure Points PC-6 and SP-3 on the Hyperemesis Gravidarum in Pregnant Women - Ria, Matilda Bupu; Manek, Brigita Dina (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Handling of nausea and vomiting in first trimester mothers (emesis gravidarum) is mostly still using pharmacological therapy, even though there is a simple event by using massage at acupuncture points to treat emesis gravidarum. The purpose of this study was to analyze the effectiveness of PC-6 and SP-3 acupressure on emesis gravidarum in first trimester pregnant women. Subjects and Method: This study is a quasi-experimental research design using a control group pretest-posttest design. The study was conducted in July-August 2021. The population in this study were all pregnant women who experienced nausea and vomiting in the 1st trimester in the Nurobo Health Center Work area, Malacca Regency. A total of 40 pregnant women in the 1st trimester were used as samples which were divided into 4 groups of 10 people each, namely group 1 (PC-6 acupressure), group 2 (SP-3 acupressure), group 3 (combination of PC-6 and SP-3 acupressure), and group 4 or control group (vitamin B6). The sample was selected by consecutive sampling technique. Data analysis using Wilcoxon Rank-Test and Paired T-Test. Results: After intervention of accupressure in PC-6 point, SP-3 point, or combination of both PC-6 and SP-3 reduced frequency of vomiting and nausea and duration of nausea. Conclusion: accupressure in PC-6 point, SP-3 point, or combination of both PC-6 and SP-3 reduce frequency of vomiting and nausea and duration of nausea in pregnant women.